The effective polycyclic aromatic hydrocarbons removal from waste cooking oils: the best evidence review - Mohd Hanafi, Mohd Hafidzal; Ab Razak, Nurul Afwanisa`; Razak, Nurul Hanim; Ibrahim, Asriana; Omar, Anis Ainaa (Italian Association of Chemical Engineering - AIDIC, 2021)
Polycyclic aromatic hydrocarbons (PAHs) are a large group of organic compounds that consist of two or more aromatic rings. PAHs are produced during incomplete combustions of hydrocarbons. Apart from being identified as carcinogenic and mutagenic, PAHs pose a high potential to cause severe health and environmental issues. Oils and lipid matrices, such as Waste Cooking Oils (WCOs),may contain highly concentrated amounts of PAHs that are unsafe. Although vegetable oils are mainly free from PAHs, they are exposed to PAHs contamination from environmental sources. To date, studies on the removal of PAHs in WCOs have been limited despite that many researchers have demonstrated the increasing health risk posed by WCOs. Therefore, this review aims to discuss the best-recommended method to treat WCOs, particularly for removing PAHs. A selected number of the most common biological and physical/chemical treatment methods for PAHs removal were reviewed. In short, this review concluded that the adsorption method using 1 % activated charcoal for 35 min at 110 °C under vacuum bleaching operation at 30 mbar to 35 mbar was considered the most approach to remove PAHs. The method successfully removed 99.7 % of benzo[a]pyrene, signifying the potential application of Activated Carbon (AC) to remove PAHs in WCOs.